Buffered charcoal-yeast extract medium for the isolation of brucellae. - Raad, I (1990)
A patient with chronic osteomyelitis caused by Brucella abortus had negative agglutination titers. Because of a superimposed staphylococcal infection that resulted in the overgrowth of this organism on nonselective media, brucellae were isolated only on a selective buffered charcoal-yeast extract (BCYE) agar. Sixteen strains of various Brucella species were inoculated on BCYE agar; selective BCYE agar with polymyxin, anisomycin, and cefamandole; and brucella blood agar. The growth and recovery rates on the three media tested were comparable for 14 strains. BCYE agar with polymyxin, anisomycin, and cefamandole may be useful as a selective medium for the isolation of brucellae.